Urinary tract infection in an older patient: a case study and review. (2nd April 2023) - Read, Haley; Mortimore, Gerri
Abstract : This article will discuss and reflect on a case study involving the prescribing of nitrofurantoin, by a non-medical prescriber, for a suspected symptomatic uncomplicated urinary tract infection in a patient living in a care home. The focus will be around the consultation and decision-making process of prescribing and the difficulties faced when dealing with frail, uncommunicative patients. This article will explore and critique the evidence-base, local and national guidelines, and primary research around the pharmacokinetics and pharmacodynamics of nitrofurantoin, a commonly prescribed medication. Consideration of the legal, ethical and professional issues when prescribing in a non-medical capacity will also be sought, concluding with a review of the continuing professional development required to influence future prescribing decisions relating to the case study. Urinary tract infections are common in older people. Haley Read and Gerri Mortimore describe the decision making process in the case of an older patient with a UTI